Preparation and Properties of Magnetic Molecularly Imprinted Polymers and Their Use as Adsorbents for Selective Adsorption of Indole - Dandan Niu; Zhiping Zhou; Chen Wu; Wanzhen Xu (Adsorption Science & Technology)
A novel method for selective adsorption of indole using magnetic molecularly imprinted polymers (MMIPs) as the adsorbent is proposed in this work. The MMIPs were synthesized by microemulsion polymerization, using Fe 3 O 4 nanoparticles as the magnetically susceptible component, acrylamide as the functional monomer, ethylene glycol dimethacrylate as the cross-linker and indole as template molecule. The products obtained were characterized by Fourier transform infrared spectroscopy, transmission electron microscopy, vibrating sample magnetometry and thermogravimetric analysis. The adsorption performances of MMIPs were investigated by batch adsorption experiments in terms of selective recognition, adsorption kinetics and adsorption isotherms, respectively. The maximum amount of adsorption on MMIPs occurs at approximately 120 minutes. The results indicate that MMIPs possess high adsorption capacity for indole. The adsorption fits with the pseudo-second-order kinetic model and the Langmuir isotherm model.